De território a paisagem: o que é "paisagem"? - Fauvrelle, Natália (2018)
In this paper we examine the concept of landscape and some issues related to its understanding, reection which is associated to our Ph.D. in Museology, whose subject is the world heritage landscape of the Alto Douro Wine Region. By doing the conceptual exploration of the term we veried its density, with various interpretations and multiple meanings. Starting from the questions how the territory has become landscape? and what is the landscape? we aim to understand this concept from dierent perspectives, analysing its evolution and the way it was considered in dierent disciplines. At the same time, we will discuss the understanding of the landscape from a phenomenological interpretation, emphasizing direct and entailed contact with the landscape and its builders.